Biological Control of Apple Anthracnose by Paenibacillus polymyxa APEC128, an Antagonistic Rhizobacterium - Young Soo Kim; Kotnala Balaraju; Yongho Jeon (The Plant Pathology Journal, 2016)
The present study investigated the suppression of the disease development of anthracnose caused by Colletotrichum gloeosporioides and C. acutatum in harvested apples using an antagonistic rhizobacterium Paenibacillus polymyxa APEC128 (APEC128). Out of 30 bacterial isolates from apple rhizosphere screened for antagonistic activity, the most effective strain was APEC128 as inferred from the size of the inhibition zone. This strain showed a greater growth in brain-heart infusion (BHI) broth compared to other growth media. There was a reduction in anthracnose symptoms caused by the two fungal pathogens in harvested apples after their treatment with APEC128 in comparison with non-treated control. This effect is explained by the increased production of protease and amylase by APEC128, which might have inhibited mycelial growth. In apples treated with different APEC128 suspensions, the disease caused by C. gloeosporioides and C. acutatum was greatly suppressed (by 83.6% and 79%, respectively) in treatments with the concentration of 1 × 10⁸ colony forming units (cfu)/ml compared to other lower dosages, suggesting that the suppression of anthracnose development on harvested apples is dose-dependent. These results indicated that APEC128 is one of the promising agents in the biocontrol of apple anthracnose, which might help to increase the shelf-life of apple fruit during the post-harvest period.